Real-Time Interaction to Increase Consumer Trust and Drive Impulse Purchases in E-Commerce - Sanjaya, Muarif; Frediansyah, Willy Redzy; Yoestini; Dirgantara, I Made Bayu (LifeSciFi, 2025)
The rapid development of e-commerce in Indonesia has driven significant shifts in consumer behavior, particularly among Generation Z who are known to be responsive to technology and immersive digital experiences. This study aims to systematically evaluate the influence of real-time interactions on consumer trust formation and impulse purchase behavior in the context of e-commerce. Using the PRISMA protocol-based Systematic Literature Review (SLR) method through the Watase Uake website, data obtained through analysis of scientific articles from reputable journals published between 2022-2025 were analyzed thematically and methodologically. The results show that features such as live streaming, real-time chat, and dynamically personalized content are able to increase perceptions of authenticity, emotional closeness, and responsiveness that significantly strengthen trust and trigger impulse buying. Consumer trust is shown to be a key mediating variable that bridges the relationship between digital engagement and spontaneous purchase decisions. The findings confirm the importance of value-based marketing approaches and authentic engagement specifically designed to meet Generation Z's digital expectations. This study makes a conceptual contribution to the digital consumer behavior literature and offers strategic guidance for e-commerce practitioners in designing adaptive, ethical and trust-based user experiences.